Ten Strategies to Reduce Gender Inequality at Scientific Conferences - Sardelis, Stephanie; Oester, Samantha; Liboiron, Max (Frontiers in Marine Science, 2017)
Conferences organized by professional societies provide scientists and industry professionals with an excellent opportunity to disseminate their work, network with like-minded researchers, and form collaborative relationships for future endeavours. However, these opportunities are rarely distributed equally between women and men in science. Addressing gender inequity should be a primary consideration for all societies hosting conferences. Yet, many STEM conferences are struggling with gender biases and the understanding that gender inequity also applies to non-binary gender identities and intersectional diversityoverlapping social identities. At the Society for Conservation Biology’s 4th International Marine Conservation Congress (IMCC4), “Promoting the Participation of Women at Science Conferences” was one of four focus groups of the IMCC4 Diversity Focus Group Series. This paper outlines ten feasible and realistic intervention strategies delineated during the Women at Science Conferences focus group discussion as positive encouragement for professional societies to continue towards gender equity. The ten interventions to reduce for gender inequity at conferences include: adopting community principles and a Code of Conduct,; appointing a Safety Officer,; requiringe a registration honour system pledge and conduct surveys,; offering a mentorship program,; organizinge focus groups,; givinge benefits for participating in diversity programming,; assisting with child care,; proffering travel grants,; providinge badges on lanyards,; and randomizinge the conference program. These strategies are intended to reduce participation barriers for women scientists at conferences, and range in the amount of planning they require to provide options for all societies, regardless of their fiscal or labour capacity.